Low level of selenium increases the efficacy of 24-epibrassinolide through altered physiological and biochemical traits of Brassica juncea plants. (15th October 2015) - Naz, Fatima Salva; Yusuf, Mohammad; Khan, Tanveer A.; Fariduddin, Qazi; Ahmad, Aqil
Highlights: Selenium (Se) showed dual response in terms of growth, photosynthesis and antioxidants. High levels of Se diminish growth, photosynthesis and disturbed water relations. 24-Epibrassinolide (EBL) has potential to confer tolerance against toxic level of selenium. EBL mitigated the deleterious action of selenium toxicity. Duos of Se and EBL enhanced the antioxidants and proline more than the non-treated control plants. Abstract: This study was conducted to provide an insight into the effect of Se (through soil) induced changes in Brassica juncea plants in the presence and absence of 24-epibrassinolide (EBL; foliar). The Se treatments showed dual response, 10 μM of Se significantly increased growth, water relations, photosynthetic attributes along with carbonic anhydrase activity whereas its higher concentrations proved inhibitory in concentration dependent manner. The follow-up application of EBL to the Se stressed plants improved growth, water relations, photosynthesis and simultaneously enhanced the various antioxidant enzymes viz. catalase, peroxidase and superoxide dismutase with the excess accumulation of proline. In addition to this, 10 μM Se increases the efficacy of 10 −8  M of EBL and both in combination showed maximum increase for the growth and photosynthetic traits of plants. On the other hand, the elevated level of antioxidant enzymes as well as proline could have conferred tolerance to the Se-stressed plants resulting in improved growth, water relations and photosynthesis.